Development of autonomous navigation in structured environment for mobile robot - Ab Lafit, Mohd Syakirin (2005)
This paper presents the development of autonomous navigation for mobile robot in structured environment. The robot is controlled by a CPM2A Programmable Logic Controller (PLC) series micro controller that can be programmed. The inputs variables for the controller are photoelectric sensor and limit switches. Sensors play an important role in this project because the controlling parts of the robot depend on sensors that will detect any conditions that are set upon. The robot has to complete a critical task and also all the movement depending on the task given to accomplish the objective. The scope of this project is to design and construct the mobile robot with the sequences of task known as "partner robot''.